THE USE OF PICTURES TO DEVELOP WRITING SKILLS OF THE EIGHTH GRADE STUDENTS OF SMP SATAP NEGERI 1 AMPIBABO - Mandalika, Leni; Jamiluddin, Jamiluddin; Mashuri, Mashuri (Tadulako University, 2024)
The objective of this research was prove that the use of pictures can develop the students skill to write recount text. The research applied quasi experimental research design that involved experimental group and a control group. The sample of this research was 45students, which where divided into 22 students of class A as the experimental group and 23 students of class B as the control group. The sample was selected by using purposive sampling technique. In collecting the data, the researchers used test, the test was used pre-test and post-test. Then, the data were analyzed statistically. Having analyzed the data, it was revealed that there were different score obtained from control group and experimental group. In other words, t-counted (3,70) was higher than t-table (1,681). It means that the research hypothesis is accepted. In conclusion, that the use of pictures can develop the students writing skill to the eighth grade of SMP SATAP Negeri 1 Ampibabo.